2018
DOI: 10.1021/acscatal.8b02521
|View full text |Cite
|
Sign up to set email alerts
|

The Active Sites in the Phillips Catalysts: Origins of a Lively Debate and a Vision for the Future

Abstract: In this work, we summarize and critically compare some of the experimental results recently published on the Phillips catalyst, in the attempt to make the point on a few particularly debated questions that have recently animated the specialized literature; in particular, we discuss the structure of the active chromium sites and how ethylene polymerization initiates on them. The data collected in this article unequivocally demonstrate that the structural and electronic properties of the chromium sites strongly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
75
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 153 publications
(450 reference statements)
1
75
0
Order By: Relevance
“…This is only possible by EXAFS discussed below. The very weak prepeak at 5986 eV was assigned to a Cr II state as well by Groppo et al . and can only be unequivocally observed for the activator MMAO.…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…This is only possible by EXAFS discussed below. The very weak prepeak at 5986 eV was assigned to a Cr II state as well by Groppo et al . and can only be unequivocally observed for the activator MMAO.…”
Section: Resultsmentioning
confidence: 57%
“…The corresponding XANES spectra show an increased splitting between the prepeak shoulder, now around 5990.5 eV, and the main edge (Table ). Since the detection limit for a minor fraction in XANES spectra was estimated to 10 % by Groppo et al . it can thus be concluded that the prepeak shoulder at 5992.0 eV is the signature of Cr II in the present system.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…[ 6 ] The active center is susceptible to the electronic structures and coordination environments, that a small change in the coordination environment can impact the polymerization performance and the properties of the final product. [ 7 ] Therefore, two strategies were applied in the field throughout the years. A usual method is to introduce new components on the SiO 2 support to produce a more favorable coordination environment.…”
Section: Introductionmentioning
confidence: 99%
“…For the support CrO x /SiO 2 Phillips catalyst, the molecular structure of chromate has been reported to exist in the forms of mono‐, dichromate, or even polychromate. [ 7 ] Rebenstorf and Larsson [ 14 ] determined that the catalyst surface was a bis‐chromate structure by the CO bridge bond adsorption on the Phillips catalyst at low temperature in the infrared spectrum. According to Raman spectroscopy and diffuse reflectance spectroscopy, Weckhuysen et al [ 10 ] inferred that the industrially applied Cr/Silica catalysts existed in the form of monochromates, while at higher chromium loadings, polychromates also occurred.…”
Section: Introductionmentioning
confidence: 99%